Immunogenicity and safety evaluation of bivalent types 1 and 3 oral poliovirus vaccine by comparing different poliomyelitis vaccination schedules in China: A randomized controlled non-inferiority clinical trial. Issue 6 (3rd June 2017) - Qiu, Jingjun; Yang, Yunkai; Huang, Lirong; Wang, Ling; Jiang, Zhiwei; Gong, Jian; Wang, Wei; Wang, Hongyan; Guo, Shaohong; Li, Chanjuan; Wei, Shuyuan; Mo, Zhaojun; et al.
ABSTRACT: Background : The type 2 component of the oral poliovirus vaccine is targeted for global withdrawal through a switch from the trivalent oral poliovirus vaccine (tOPV) to a bivalent oral poliovirus vaccine (bOPV). The switch is intended to prevent paralytic polio caused by circulating vaccine-derived poliovirus type 2. We aimed to assess the immunogenicity and safety profile of 6 vaccination schedules with different sequential doses of inactivated poliovirus vaccine (IPV), tOPV, or bOPV. Methods : A randomized controlled trial was conducted in China in 2015. Healthy newborn babies randomly received one of the following 6 vaccination schedules: cIPV-bOPV-bOPV(I-B-B), cIPV-tOPV-tOPV(I-T-T), cIPV-cIPV-bOPV(I-I-B), cIPV-cIPV-tOPV(I-I-T), cIPV-cIPV-cIPV(I-I-I), or tOPV-tOPV-tOPV(T-T-T). Doses were administered sequentially at 4–6 week intervals after collecting baseline blood samples. Patients were proactively followed up for observation of adverse events after the first dose and 30 days after all doses. The primary study objective was to investigate the immunogenicity and safety profile of different vaccine schedules, evaluated by seroconversion, seroprotection and antibody titer against poliovirus types 1, 2, and 3 in the per-protocol population. Results : Of 600 newborn babies enrolled, 504 (84.0%) were included in the per-protocol population. For type 1 poliovirus, the differences in the seroconversion were 1.17% (95% CI = −2.74%, 5.08%) between I-B-B and I-T-T and 0.00% (95% CI: −6.99%, 6.99%) between I-I-B and I-I-T; for type 3 poliovirus, differences in the seroconversion were 3.49% (95% CI: −1.50%, 8.48%) between I-B-B and I-T-T and −2.32% (95% CI: −5.51%, 0.86%) between I-I-B and I-I-T. The non-inferiority conclusion was achieved in both poliovirus type 1 and 3 with the margin of −10%. Of 24 serious adverse events reported, no one was vaccine-related. Conclusions : The vaccination schedules with bOPV followed by one or 2 doses of IPV were recommended to substitute for vaccinations involving tOPV without compromising the immunogenicity and safety in the Chinese population. The findings will be essential for policy formulation by national and global authorities to facilitate polio elimination.